Evidence-Based Offender Profiling - Fox, Bryanna; Farrington, David P.; Kapardis, Andreas; Hambly, Olivia (Milton : Routledge, 2020)
Offender profiling is an investigative tool used to narrow down the range of potential suspects for a crime by predicting the personality, behavioral, and demographic characteristics that an offender is likely to possess, based upon information collected at the crime scene. While offender profiling has been popularized by TV shows and movies such as Criminal Minds, Silence of the Lambs, and Mindhunter, the real-world impact of offender profiling is largely unknown. This book discusses the history of offender profiling, summarizes research on offender profiling methods, and reviews offender profiling evaluations of accuracy and applied impact. This book also describes a promising new offender profiling methodology called evidence-based offender profiling. This new method relies upon empirical data and scientific methods to develop, evaluate, and replicate offender profiles, thereby increasing offender profiling's accuracy and utility for active police investigations. It uses prior information about statistical regularities between types of offenders and types of offenses to predict the characteristics of offenders in unsolved cases. A discussion of the future of offender profiling research and implications for law enforcement is also included. This book also explains how practitioners can benefit from the use of empirically tested and validated profiles in their unsolved investigations and how the use, continued research, and evaluation of evidence-based offender profiling can advance the quality, prestige, and utility of the field of offender profiling.
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Acknowledgements -- Foreword -- 1 Introduction to Evidence-Based Offender Profiling -- 2 Development of offender profiling -- 3 Progress towards evidence-based offender profiling -- 4 Evidence-based offender profiles and evaluations in the United States -- 5 International replication of evidence-based offender profiles in the United Kingdom -- 6 The future of evidence-based offender profiling -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Criminal behavior, Prediction of; Criminal psychology; Criminal behavior; PSYCHOLOGY / Forensic Psychology; LAW / Forensic Science